Effects of Sodium Azide on Yield Parameters of Chickpea (Cicer arietinum L.) - Vijay S. Kothekar, Mahesh P. Kulthe1* and (Journal of Phytology, 2011)
The mutagenic effects of different concentrations of sodium azide (0.01%, 0.02% and 0.03%) on chickpea (Cicer arietinum L.) varieties Akash and Vishal were investigated. The characters studied include; days of flowering, days to maturity, plant height, number of pods per plant, number of seeds per plant and hundred seed weight in M2 and M3 generations. Both negative and positive shifts in mean values were recorded as a result of the chemical treatment. The results indicate the possibilities of evolving higher yield variants through proper selection. Thus, economic traits like days to maturity, number of pods per plant, number of seeds per plant and hundred seed weight in M3 generation offer scope for selection and improvement. Key words: Chickpea, Mutagenic effects, Sodium azide <span style="font-weight: normal; font-size: 7pt; line-height: 110%; font-family: ";Book Antiqua";,";serif";; letter-spacing: -0.3pt; font-variant: normal! important; mso-fareast-language: EN-SG; mso-font-kerning: 0pt; mso-no-proof: no; mso-ansi-language: EN-SG;" lang="EN-SG">Mahesh P. Kulthe and Vijay S. Kothekar. Ã‚Â Effects of Sodium Azide on Yield Parameters of Chickpea (Cicer arietinum L.). J Phytol 2/3 (2011) 39-42.